TRANSFORMING TRADITIONS: THE JOURNEY OF PICHWAI ART OF NATHDWARA FROM RELIGIOUS ROOTS TO MODERN SPACES - Jyoti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper examines the evolutionary journey of Pichwai Art from its religious roots in Nathdwara, Rajasthan, to its current secular manifestations. The purpose of this study is to trace how Pichwai art, originally intended for temple worship, has transitioned to contemporary spaces while retaining its cultural and spiritual significance. Using historical analysis and visual investigation, the research explores the intricate patterns and vibrant motifs of Pichwai art, such as lotuses, peacocks, and Krishna’s flute, and their symbolic meanings. The methodology includes a review of literature, fieldwork. The findings reveal the challenges faced by artists due to secularization and propose strategies for conserving this traditional art form. This study concludes that despite modernization, Pichwai art continues to thrive, reflecting its adaptability and enduring appeal.